Institutional Accountability of Nonstate Actors in the UNFCCC: Exit, Voice, and Loyalty. Issue 1 (28th November 2016) - Kuyper, Jonathan; Bäckstrand, Karin; Schroeder, Heike
Abstract: How are nonstate actors within the United Nations Framework Convention on Climate Change (UNFCCC) held to account? In this article, we introduce the concept of "institutional accountability" to complement the wider literature(s) on accountability in climate governance. Within institutional frameworks, actors employ rules, norms, and procedures to demand justifications from one another. In light of those justifications, actors then use "exit, voice, or loyalty" to positively or negatively sanction each other. To depict the dynamics of institutional accountability, we analyze the role of nonstate actors in the nine constituency groups of the UNFCCC. We outline the constituency structure and the population of observer organizations. We then identify examples where nonstate actors employed institutional rules in tandem with exit, voice, or loyalty to foster accountability. In making this analysis we draw upon three years of on‐site participation at UNFCCC meetings, document analysis, and more than 40 semi‐structured interviews with state and nonstate actors. We conclude by discussing the scope and conditions under which institutional accountability may occur in other issue areas of global governance.